Detection and sequencing of Potato virus Y (PVY) and Potato leafroll virus (PLRV) in a volunteer plant of Solanum tuberosum L. cv. Diacol-Capiro (2017)
Viral diseases are among the most limiting factors in the production of potato in Colombia and the rest of the world. The best strategy to control plant viruses consists on the use of certified seed tubers, control of arthropod vectors and the use of adequate crop management practices that reduce mechanical transmission and the presence of viral reservoirs like weeds and volun-teer plants. However, the successful implementation of these practices relies on the availability of highly sensitive techniques that allow for the asymptomatic detection of viruses. In this work, we tested the performance of Next-generation sequencing (NGS) and real time RT-PCR (RT-qPCR) on a single volunteer potato plant (cv. Diacol-Capiro) growing naturally in a seed-tuber storage facility in Yarumal (Antioquia). Our NGS results demonstrate a mixed infection with Potato virus Y (PVY) and Potato leafroll virus (PLRV). RT-qPCR was performed in roots, main stolons, crown (root collar) and upper, middle and lower leaves using specific primers for PVY, PLRV, Potato virus S (PVS), Potato virus V (PVV), Potato virus X (PVX) and Potato yellow vein virus (PYVV). Only PVY and PLRV were detected in good agreement with the NGS data. This work demonstrates the use-fulness of both techniques for supporting integrated management of plant viruses in potato, in-cluding virus detection in natural reservoirs such as volunteer plants and weeds.